The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1128/iai.72.11.6245-6254.2004
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the Trypanosoma cruzi Sequence Database for Identification of Potential Vaccine Candidates by In Silico and In Vitro Screening

Abstract: Glycosylphosphatidylinositol (GPI)-anchored proteins are abundantly expressed in the infective and intracellular stages of Trypanosoma cruzi and are recognized as antigenic targets by both the humoral and cellular arms of the immune system. Previously, we demonstrated the efficacy of genes encoding GPI-anchored proteins in eliciting partially protective immunity to T. cruzi infection and disease, suggesting their utility as vaccine candidates. For the identification of additional vaccine targets, in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
111
0
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(115 citation statements)
references
References 43 publications
1
111
0
3
Order By: Relevance
“…This high throughput approach has been successfully used to propose promising vaccine targets for prokaryote pathogens such as Neisseria meningitides [35] and Streptococcus agalactiae [36]. Reverse vaccinology has also been used for identifying potential vaccine candidates in the protozoa Trypanosoma cruzi and Leishmania [37][38][39]. Use of this approach in more complex eukaryotic pathogens such as schistosomes, however, suffers from several drawbacks: (1) deduction of ORFs from genomes of most eukaryotes is not straightforward owing to mRNA splicing.…”
Section: Introductionmentioning
confidence: 99%
“…This high throughput approach has been successfully used to propose promising vaccine targets for prokaryote pathogens such as Neisseria meningitides [35] and Streptococcus agalactiae [36]. Reverse vaccinology has also been used for identifying potential vaccine candidates in the protozoa Trypanosoma cruzi and Leishmania [37][38][39]. Use of this approach in more complex eukaryotic pathogens such as schistosomes, however, suffers from several drawbacks: (1) deduction of ORFs from genomes of most eukaryotes is not straightforward owing to mRNA splicing.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that prophylactic vaccination before challenge infection (11)(12)(13)(14) or treatment of chronically infected experimental animals with the antiparasite drug benznidazole (15), which resulted in the host's ability to control acute parasitemia and tissue parasite burden (11)(12)(13)(14), consequently prevented myocardial oxidative and inflammatory pathology (15)(16)(17) and led to preservation of the hemodynamic function of the heart (15). Because oxidative/inflammatory adducts result in cellular damage, we hypothesize that the damage-associated molecular patterns (DAMPs) are released in the peripheral blood and can be captured by the phagocyte activation pattern.…”
mentioning
confidence: 99%
“…Traditionally, such targets of B-cell responses have been identified from parasites through serological screening of an expression library or by immunoblotting of crude lysate separated by two-dimensional gel electrophoresis. In contrast, only a few attempts have been made to computationally predict serological antigens of pathogens from the proteome based on their sequences, such as predicting secreted or surface proteins (4,11) and identifying proteins with ␣-helical coiled-coil domains (61). Although the prediction of secreted or surface proteins has shown some promise in identifying antigens from T. cruzi (11), it may not be powerful enough to reduce the number of candidates to a practical level when dealing with the whole genome.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, only a few attempts have been made to computationally predict serological antigens of pathogens from the proteome based on their sequences, such as predicting secreted or surface proteins (4,11) and identifying proteins with ␣-helical coiled-coil domains (61). Although the prediction of secreted or surface proteins has shown some promise in identifying antigens from T. cruzi (11), it may not be powerful enough to reduce the number of candidates to a practical level when dealing with the whole genome. There are 3,141 T. cruzi genes containing sequences encoding predicted signal peptides, 5,169 with transmembrane domains, and 1,776 containing both.…”
Section: Discussionmentioning
confidence: 99%